Calculus : global edition - Briggs, William L., ....-; Cochran, Lyle, ....-; Gillett, Bernard, ....-; Schulz, Eric, ....- (Boston : Pearson, 2015)
This much anticipated second edition of the most successful new calculus text published in the last two decades retains the best of the first edition while introducing important advances and refinements. Authors Briggs, Cochran, and Gillett build from a foundation of meticulously crafted exercise sets, then draw students into the narrative through writing that reflects the voice of the instructor, examples that are stepped out and thoughtfully annotated, and figures that are designed to teach rather than simply supplement the narrative. The authors appeal to students' geometric intuition to introduce fundamental concepts, laying a foundation for the development that follows. The groundbreaking eBook contains over 650 Interactive Figures that can be manipulated to shed light on key concepts.
Authorized adaptation from the United States edition: Calculus, 2nd edition, 9780321954350
Keywords: Integraalrekening; Differentiaalrekening